Teorie e critica comparatistica (Comparatismi, 2020)
In questo breve intervento conclusivo l’autore riprende le linee principali del dibattito, sottolineando la necessità di un profondo rinnovamento degli studi letterari, e delineando un significato più ampio per la comparatistica in rapporto all’esperienza.__In this brief article, Giovanni Puglisi takes up the main points of the debate as presented in the articles that precede it, emphasizing the need for a renewal of literary studies, and outlining a broader meaning for Comparative Literature studies in relation to experience.
Keywords: Letterature comparate; Riforma dei saperi; Piacere del testo; Estetica; Nuovo uma-nesimo; Comparative Literature; Reform of knowledge; Pleasure of the text; Aesthetics; New Humanism